リュツォ ホルムワン トウガン ノ ヒョウガ リュウドウ ソクテイ ニホン ナンキョク チイキ カンソクタイ ノ ホウコク - 藤原, 健蔵; フジワラ, ケンゾウ; 吉田, 栄夫; ヨシダ, ヨシオ; FUJIWARA, Kenzo; YOSHIDA, Yoshio (国立極地研究所, 1972)
P(論文) An attempt was made at the measurements of surface velocities of ice flow in several places along the east coast of Lutzow-Holm Bay in 1960 and 1961. Difficulties in preserving stakes and in selecting suitable sites for surveying and the limited time prevented the authors from making complete measurements. Sporadic results obtained during the above period may be insufficient for the detailed discussion on water mass balance of the region. Nevertheless, they can afford a clue to that problem, because they were obtained from various places including glaciers of small to large size and sheet flow which may be representative of the ice coast. Changes in positions of bamboo stakes were determined by triangulation with a Wild T_2 theodolite. Base lines were set up on ice-free areas. Sheet flow was measured on the margin of ice sheet at a distance of 900m from a coast line of the Ongul Strait. It revealed that there was a considerable difference between flow velocities in the warm season and those in the cold season. If seasonal changes are taken into consideration, flow rates are estimated as 10.0 to 3.2m・year^<-1>, according to the localities of stakes. The Langhovde Glacier with a small floating ice tongue may flow at a rate of 172m・year^<-1>, assuming the mean annual velocity to be twice as large as the velocity in the cold season. At the Hamna Glacier which may override higher subglacial rocks between Hamna and Breidvagnippa than in the case of other glaciers only one stake could be surveyed. The stake set up on the ice close (200m) to a rock exposure showed a movement at a rate of 1.5cm・day^<-1>. The Hamna Ice Fall is a small distributary of the Hamna Glacier and its velocity near the snout was only 2.6m・year^<-1>. The Shirase Glacier is the largest ice stream on the coast of Lutzow-Holm Bay and pours into the bay head. Its movements were measured on the marginal part of its floating ice tongue near Insteodden. The measured rate reached 569 to 608cm・day^<-1> which corresponds ...